PENGEMBANGAN SISTEM TRACER STUDY MENGGUNAKAN AGILE DEVELOPMENT METHODS PADA IBK NITRO - Muhammad Ikhwan Burhan; Fadliyani Nawir; Karta Negara Salam (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2022)
The Nitro Institute of Business and Finance has made various efforts to produce quality graduates who can compete in the world of work, including carrying out tracer studies to map the needs of the world of work with the competencies taught. However, in its implementation, the tracer study is not effective and has many obstacles because it is still carried out manually and is very simple. One of the efforts made to optimize and overcome these obstacles is to develop a website-based system that is able to support the process of distributing and filling out questionnaires, storing data, and facilitating reporting. Agile Development Methods with the Extreme Programming framework are used in the development of the tracer study system at the Nitro Business and Finance Institute because it is adaptive and responsive to changes, and the development process only takes a relatively short time without compromising the quality of the system. Based on the stages of system development using Agile Development Methods with the Extreme Programming framework, there have been three iterations of the development phase. The first iteration produces an initial prototype according to user requirements; the second iteration produces an advanced prototype with the addition of several user requirements; and the third iteration produces a system that is ready for release and has met all user requirements. Keywords: Tracer Study, Agile Deveplopment Methods, Extreme Programming.